Designing for diversity : The role of reading strategies in interactive vocabulary in a digital reading environment for fifth-grade monolingual English and bilingual students - Bridget Dalton; C. Patrick Proctor; Paola Uccelli; Elaine Mo; Catherine E. Snow (Journal of Adolescent and Adult Literacy, 2011)
This study examined the relative contribution of reading comprehension strategies and interactive vocabulary in Improving Comprehension Online (ICON), a universally designed web-based scaffolded text environment designed to improve fifthgrade monolingual English and bilingual students’ reading achievement. Seventy-five monolingual English and 31 bilingual students from six classrooms were assigned to one of three ICON conditions: reading comprehension strategies, vocabulary, or a combined version of comprehension strategies and vocabulary. Students read eight multimedia folktales and informational texts within their respective ICON condition and completed embedded activities, researcher measures of comprehension and vocabulary, and pre- and postintervention standardized reading achievement tests. ANCOVA results indicated that after controlling for initial reading achievement, there was a main effect for condition on the researcher measure of vocabulary, with the combination group and vocabulary groups both significantly outperforming the strategy group. There was also an interaction effect, with differences between monolingual and bilingual Spanish-speaking students greatest in the strategy group. There was no effect of condition on comprehension, nor was there an effect of language status on narrative comprehension. However, there was a main effect of language status on expository text comprehension and standardized vocabulary achievement, with monolingual students performing more strongly than bilingual Spanish-speaking students. The results add to a growing body of research on the design and use of scaffolded digital text for diverse learners.   Keywords :  comprehension, vocabulary, technology, bilingual, English language learner, universal design for learning, e-text
Keywords: compréhension; grade 5; lecture numérique

Semiotic Representations: Building Complex Literacy Practices through the Arts - Cowan, Kay; Albers, Peggy (Reading Teacher, 2006)
Learning to write well often proves to be one of the most difficult areas in the English language arts for young children. However, in these fourth- and fifth-grade language arts classrooms, children are offered opportunities to explore, think through, and express meaning across and within sign systems--in particular, using art, drama, and language. Children engage in arts- and language-based lessons and develop semiotic texts that are richly complex and imaginatively descriptive. Within the teacher's semiotic approach to literacy instruction, children develop habits in strategy use and knowledge of and practice in sign systems, both of which help them develop strong literacy practices. Once such experiences become habits of mind, students develop new insights into their own writing, creating, and talking about their texts, as well as the composing process. (Contains 9 figures.)
Keywords: arts; enseignement des arts; grade 4; grade 5; literacy; poésie; sémiotique; théâtre